2009
DOI: 10.1097/aog.0b013e31819bdc93
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Domestic Violence in a Pregnant Military Population

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…This is consistent with our previous study of a pregnant military population screened at initial entry for prenatal care, which found that separated/divorced women were at increased risk of abuse by a partner or important person. 22 However, our current study did not find an increased risk for physical or emotional abuse in single or never-married women when compared with married women. Although causality is not demonstrated, separated and divorced women and women with a history of abuse may be more likely to be in strained or abusive relationships, or have a history of such relationships that lead to separation or divorce.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…This is consistent with our previous study of a pregnant military population screened at initial entry for prenatal care, which found that separated/divorced women were at increased risk of abuse by a partner or important person. 22 However, our current study did not find an increased risk for physical or emotional abuse in single or never-married women when compared with married women. Although causality is not demonstrated, separated and divorced women and women with a history of abuse may be more likely to be in strained or abusive relationships, or have a history of such relationships that lead to separation or divorce.…”
Section: Discussioncontrasting
confidence: 84%
“…Our previous observational prevalence study of a pregnant military population presenting for routine prenatal care (mostly women in the first trimester of pregnancy) had a 14.5% prevalence of domestic violence. 22 The higher prevalence of domestic violence (22.6%) in our current study of pregnant women presenting for emergency care may have been due to the fact that women were screened at a later time in their pregnancies, with a mean gestational age of 35 weeks. A previous study has shown that more women reported domestic violence during the latter part of pregnancy.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A high quality study of active duty personnel reported past-year prevalence of clinically significant physical abuse (defined as acts that result in significant impact or high potential for impact) to be 3.45% (Foran et al, 2011). Two studies of pregnant active duty females found past-year physical IPV prevalence rates of around 3% (Lutgendorf et al, 2012;Lutgendorf et al, 2009).…”
Section: Female Victimsmentioning
confidence: 99%
“…Certain military characteristics such as service branch, rank, engagement status and having left service have been shown to be associated with a range of psychosocial outcomes such as relationship satisfaction (Hendrix et al, 1995;Riggs et al, 1998), mental health (Baker et al, 2009;Cameron et al, 2016;Hatch et al, 2013;Iversen et al, 2009;Sher et al, 2012) and risk of aggressive behaviour (Jordan et al, 1992;MacManus et al, 2012;MacManus et al, 2013;MacManus et al, 2015) and may impact on risk of IPV victimisation (Cantos et al, 1994;Foran et al, 2011;Lutgendorf et al, 2009;Marshall et al, 2005;Rosen et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%